How steaming and drying processes affect the active compounds and antioxidant types of Gastrodia elata Bl. f. glauca S. chow. (July 2022) - Wu, Zhen; Gao, Ruiping; Li, Hong; Liao, Xia; Tang, Xin; Wang, Xiaogang; Su, Zhimin
Graphical abstract: Highlights: Steaming-then-drying of Gastrodia elata with five different drying techniques. Measuring total phenolics, total flavonoids, ascorbic acid, phenolics and bioactivities. Phenolic amounts and antioxidant activities were due to steaming and drying methods. Microstructure changes influenced the bioactive compounds and bioactivities. Selection of the most suitable processing method according to all measured parameters. Abstract: As both a traditional medicine and food material, fresh Gastrodia elata requires a curing process for quality improvement. The effects of steaming and various drying methods (sun-, hot-air-, microwave-vacuum-, freeze- and vacuum-drying) on the total phenolic, total flavonoid, ascorbic acid, adenosine, and phenolic compound contents, antioxidant activities (scavenging DPPH, ABTS +, OH and reducing power) and microstructures were investigated in this study. The contents of adenosine and individual phenolic compounds were analyzed using high-performance liquid chromatography. The results showed that steaming had adverse effects on the total phenolic, total flavonoid, adenosine, parishin C, vanillyl alcohol, quercetin and cinnamic acid contents, while subsequent hot-air- and freeze-drying showed compensatory effects. Steaming significantly increased the levels of gastrodin, p -hydroxybenzylalcohol, p -hydroxybenzaldehyde, parishins (A, B and E) and catechin (by 3.4-, 1.1-, 1.1-, 3.8-, 6-, 1.4- and 1.5-fold, respectively, p  < 0.05) compared to the fresh samples, which were further increased by hot-air- and freeze-drying. Hot-air- and freeze-drying significantly increased the levels of adenosine, gastrodin, p -hydroxybenzylalcohol, p -hydroxybenzaldehyde, parishins (A, B and C), vanillyl alcohol, catechin, caffeic acid, quercetin and cinnamic acid by 1.1–11.6-fold ( p  < 0.05) compared to steaming treatment. Steaming reduced all the antioxidant activities, which were restored partially by hot-air- and freeze-drying. Principal component and clustering analyses revealed the relationship among the samples, phenolics, and antioxidant activities, which suggested a steaming-then-drying action mechanism in which steaming changes enzymes and starch hydrolysis and drying promote condensation reactions. Collectively, steaming-then-hot-air- or freeze-drying is a promising method for enhancing the quality of Gastrodia elata for food applications.